Effectiveness of KPI implementation in the systems with unclear job responsibilities of employees - Ivanchenko, Nataliia (Актуальні питання економічних наук, 2025)
The lack of a clear division of employees’ job responsibilities complicates task management, increases the risk of organizational errors, and negatively affects the financial results of the enterprise. The implementation of the KPI systems enables the quantitative assessment of labour productivity, predicting performance results, and ensuring the rational allocation of resources within organizational structures with the unclear roles. The purpose of this paper is to analyze the effectiveness of using the KPI to increase management efficiency, balance workload, integrate various types of reporting, and reduce business risks. Methods. In this paper we have performed the analysis of experience of the KPI application in the companies with unclear division of responsibilities, and assessedthe impact of the performance indicators on the transparency of work processes, the accuracy of supervision over task performance, the integration of management and financial reporting and optimization of the tax burden.Results. The study confirmed that implementing the KPI system leads to increased accuracy in predicting productivity, facilitates effectiveness of tasks distribution among the employees, and benefitsto balance the workload equally. The KPI system helps to increase the transparency of work processes, reduce duplication of functions, and minimize errors, while also ensuring effective integration of management and financial reporting. The use of the KPI also reduces tax and operational risks, increases the economic security of the entity and creates conditions for more accurate strategic planning and forecasting of performance results. Conclusions. The use of the KPI system in the entities with unclearjob responsibilities is an effective tool for enhancing management efficiency, establishing a transparent organizational structure, and ensuring the economic stability of the enterprise. The study’s results can be used to optimize management processes in organizations with unclearly defined employees’ roles.